Optical properties of nanostructures - Miloslavsky, V.K.; Ageev, L.A.; Makovetsky, E.D.; Maskevich, S.A. (Functional Materials, 2008)
The paper is a brief review of optical properties of nanostructures containing metal nanoparticles. There is a deduction of some simple formulae describing optical spectra of composites containing small particles of various form. Comparison of theoretical and experimental data has been carried out. Conclusions following Mie theory of diffraction on spheres of various diameters and dielectric permittivities are discussed. Various examples of applications of nanoparticles and their influence on surrounding media are given. Представлено коротиий огляд властивостей наноструктур, яю містять металічні наночастинки. Наведено виводи деяких простих формул, що використовуються для опису оптичних спектрів композитів, які містять малі частинки різної форми. Проведено порівняння теорії з даними експерименту. Обговорюються наслідки, що витікають з теорії Мі, присвяченої дифракції на сферах різного діаметра та з різними діелектричними проникностями. Подано різноманітні приклади практичного застосування наночастинок та їхнього впливу на навколишне середовище. Представлен краткий обзор оптических свойств наноструктур, содержащих металлические наночастицы. Приведены выводы некоторых простых формул, используемых для описания оптических спектров композитов, содержащих малые частицы различной формы. Проведено сравнение теории с данными эксперимента. Обсуждаются следствия, вытекающие из теории Ми, посвященной дифракции на сферах различного диаметра и с различной диэлектрической проницаемостью. Приведены разнообразные примеры практического применения наночастиц и их воздействия на окружающую среду.